Analysis of High Step-Up Quasi-Z-Source-Based Converter With Low Input Current Ripple - Ataollah Samadian; Milad Ghavipanjeh Marangalu; Iman Talebian; Navid Hadifar; Seyed Hossein Hosseini; Mehran Sabahi; Hani Vahedi (IEEE Open Journal of the Industrial Electronics Society)
This article presents a new high step-up quasi-Z-source-based dc–dc converter with switched boost techniques and voltage multiplier cells. Compared with the conventional Z-source-based converters, this converter not only can achieve high voltage gain but also has good efficiency at high output voltage and higher output power conditions. Most of the Z-source-based converters suffer from high current stress across the power mosfets and the operation in lower power. However, the other important advantages include very low input current ripple, low voltage and current stress across the power switches, no duty ratio limitation, and leakage current elimination by providing the common grounded feature. So, in this topology, the null of the output is connected to the negative terminal of the input dc source directly. Therefore, the leakage current can be eliminated completely. As a result, the proposed converter is suitable for renewable energy sources (RESs)’ applications, such as photovoltaic (PV) systems. The mathematical analysis, operating principle for the proposed converter, and comparison with other converters are evaluated. Finally, in order to verify the accurate performance of the proposed converter and confirm the mentioned features of the proposed converter, a 1-kW laboratory prototype is built and tested.